Good Practices in Religious Moderation: A Study on The Values of Local History Education From K.H. Syadzeli Hasan - Hidayatullah; Ikhwan Hadiyyin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The aim of this research was to describe the values ​​of the fighting spirit of the one of Banten figures, namely Prof. KH. Syadzeli Hasan. The method used in this research is the biographical method with a historical approach. Then, from the data, a historical description was carried out through field research and documents explaining their struggles and life journeys. Therefore, this research data collection technique was carried out through interviews, observation, and documentation. Then the data was analysed using qualitative analysis. Based on the results of this research, it is concluded that: (1) The values ​​of their fighting spirit can be used as a lesson for society, are having the characteristics of: (a) being persistent in learning, fighting and working; (b) patriotic and love the country; (c) religious; (d) care about society; (e) leadership and (f) independence and entrepreneurial spirit (2) The public's view of the historical value of Beji figures as a source of learning for community character education is very positive, because the values ​​of the spirit of struggle possessed by these three figures are not only relevant to the government's concept regarding the design of character education programs also needed by the younger generation as a spark of inspiration.